Spiritual Blessing Energy Treatment as an Approach for Boosting Growth and Yield of Bottle Gourd (Lagenaria siceraria L.) - Trivedi, Dahryn; Dattaram Kadam, Vivek; Bapu Gaikwad, Tejas; Rajendra Phutankar, Nikhil; Mondal, Sambhu; Jana, Snehasis (Journal of Plant Genetics and Crop Research, 2026)
The objective of this study was to improve the growth and yields of bottle gourd plants after exposure with spiritual blessing energy treatment (SBET) to the seeds and land. Twenty-one morphological traits of leaves, fruit, seed, and twenty-eight phenological parameters were employed to evaluate bottle gourd’s growth and yields after SBET. Results of bottle gourd showed a diversifiable characteristic of leaves, fruits, and seeds. Nine qualitative traits exhibited with distinct differences in the biofield-energy treatment group compared to the control. At harvest, growth-related phenological parameters such as plant vine length, number of branches, internodal length, and leaf width were significantly improved in the treatment group by 65.43% (p ≤ 0.001), 51.78% (p ≤ 0.01), 49.40% (p ≤ 0.001), and 40.82% (p ≤ 0.001), respectively, compared to the control. Additionally, yield-related parameters such as number of female flowers, number of fruits per vine, and fruit yield per hectare were significantly increased by 47.73% (p ≤ 0.05), 26.52% (p ≤ 0.001), and 38.99% (p ≤ 0.05), respectively, with respect to the control. With distinct qualitative variations and high statistical significance, these results suggest that SBET may serve as a potent non-traditional intervention for optimizing phenological development and agricultural output of bottle gourd.
Keywords: spiritual blessing; prayer; morphology; phenology; bottle gourd; yield